Acceptability and Reliability of the Bayley Scales of Infant Development III Cognitive and Motor Scales among Children in Makwanpur - Manandhar, S R; Dulal, S; Manandhar, D S; Saville, N; Prost, A (Journal of Nepal Health Research Council, 2016)
Background: The Bayley Scales of Infant Development III (BSID III) is an instrument to measure the development of children aged 1-42 months. Our study sought to assess the feasibility and reliability of the BSID III’s cognitive and motor sub-scales among children in rural Nepal. Methods: For this study, translation and back translation in Nepali and English for cognitive and motor sub-scale of BSID III were done. Two testers assessed a total of 102 children aged 1-42 months and were video-recorded and rescored by the third tester. Raw scores were calculated for each assessment. Inter and intra-observer reliability of scores across the three testers was examined. Raw score was converted into scaled score to examine the mean score. The study received ethical clearance from NHRC.Results: A total of 102 children were assessed. The inter-rater reliability of the BSID III among three testers using the Intraclass Correlation Coefficient by age group was 0.997 (95% CI: 0.996-0.998) for the cognitive scale, 0.997 (95% CI: 0.996- 0.998) for the gross motor scale, and 0.998 (95% CI: 0.997- 0.999) for the fine motor scale. All were statistically significant (p< 0.0001). The mean scaled cognitive, fine motor and gross motor development scores in this group of children were 8.3 (SD: 2.5), 8.5 (SD: 2.6) and 9.5 (3.2), respectively.Conclusions: Assessing the cognitive and motor development of children under five using the BSID III was feasible in Makwanpur district, Nepal. The inter-rater reliability was highly comparable among the three testers. Keywords: Bayley scale of infant development (BSID); inter and intra -observer reliability.